2015
DOI: 10.1128/iai.00154-15
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia muridarum Induction of Glandular Duct Dilation in Mice

Abstract: Although Chlamydia-induced hydrosalpinx in women and mice has been used as a surrogate marker for tubal infertility, the medical relevance of nontubal pathologies, such as uterine horn dilation, developed in mice following chlamydial infection remains unclear. We now report that the uterine horn dilation correlates with glandular duct dilation detected microscopically following Chlamydia muridarum infection. The dilated glandular ducts pushed the uterine horn lumen to closure or dilation and even broke through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…This type of pathology was also observed in other recent studies. 6,48,49 Pathology in the oviducts, more specifically hydrosalpinx, is a known pathological marker for infertility in mice. Others have, however, also observed a correlation between infertility and uterine horn and glandular duct dilation, 49 and the TC model (using C.t.)…”
Section: Discussionmentioning
confidence: 99%
“…This type of pathology was also observed in other recent studies. 6,48,49 Pathology in the oviducts, more specifically hydrosalpinx, is a known pathological marker for infertility in mice. Others have, however, also observed a correlation between infertility and uterine horn and glandular duct dilation, 49 and the TC model (using C.t.)…”
Section: Discussionmentioning
confidence: 99%
“…The uterine horn dilation was chronic and therefore likely caused by glandular duct dilation, which may occur first, pushing into the uterine horn lumen causing uterine horn lumenal blockades at multiple sites and leading to extensive uterine horn lumenal dilation as previously reported following C . muridarum infection [ 48 ]. Although hydrosalpinx is an important pathologic marker of Chlamydia - induced infertility in mice [ 6 , 48 50 ], none of the immunized and control mice in the studies reported here developed any overt hydrosalpinx as assessed by visual examination.…”
Section: Discussionmentioning
confidence: 99%
“…The sections were stained with hematoxylin and eosin (H&E) as described elsewhere [6]. The H&E stained sections were scored for severity of inflammation and dilation based on the modified schemes established previously [6, 39, 40]. Scoring for inflammatory cell infiltrates (at the chronic stage of infection, the infiltrates mainly contain mononuclear cells): 0, no significant infiltration; 1, infiltration at a single focus; 2, infiltration at two to four foci; 3, infiltration at more than four foci; and 4, confluent infiltration.…”
Section: Methodsmentioning
confidence: 99%